Interferon γ-producing γδ T cell-dependent antibody isotype switching in the absence of germinal center formation during virus infection - Maloy, Kevin J. (The National Academy of Sciences, 1998)
Ig class switching usually occurs as a consequence of cognate interactions between antigen-specific B cells and CD4(+) αβ T cells. Vesicular stomatitis virus (VSV) infection of immunocompetent mice induces a rapid T-independent neutralizing IgM response followed by a long-lived T-dependent IgG response. Surprisingly, αβ T cell-deficient (TCRα(−/−)) mice also produced neutralizing IgG antibodies when infected with live VSV or with a recombinant vaccinia virus expressing the VSV glycoprotein (Vacc-IND-G), but not when immunized with UV-inactivated VSV (UV-VSV). The neutralizing IgG responses did not require the presence of NK cells or complement, but were crucially dependent on IFN-γ and were predominantly of the IgG2a isotype. IgG production depended on residual CD3(+) non-αβ T cell populations present in the TCRα(−/−) mice, which produced IFN-γ upon in vitro stimulation. A key role for γδ T cells was confirmed by the fact that TCRβ(−/−) mice also generated strong neutralizing IgG responses to VSV, whereas TCRβ(−/−)δ(−/−) mice produced very low titers. The neutralizing IgG responses of TCRα(−/−) mice were accompanied by the development of memory B cells, but not by antigen-specific germinal center (GC) formation. Thus, during viral infection of αβ T cell-deficient mice, γδ T cells may provide the signals that are required for isotype switching.